2021
DOI: 10.1128/mbio.02714-21
|View full text |Cite
|
Sign up to set email alerts
|

YhdP, TamB, and YdbH Are Redundant but Essential for Growth and Lipid Homeostasis of the Gram-Negative Outer Membrane

Abstract: Gram-negative bacteria like Escherichia coli are characterized by having two membranes. Systems required for the biogenesis of the Gram-negative outer membrane have been identified except for that required for the transport of newly synthesized phospholipids from the inner to the outer membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(108 citation statements)
references
References 86 publications
8
85
0
Order By: Relevance
“…Lastly, YhdP has been implicated in GPL transport as loss of YhdP slows IM rupture in a high flux GPL transport background [ 6 ]. Furthermore, a recent publication also reveals the essentiality and redundancy of YhdP, TamB, and YdbH [ 37 ]. The authors also demonstrate a disruption in OM lipid homeostasis in yhdP tamB mutants, but do not establish defects in GPL transport [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, YhdP has been implicated in GPL transport as loss of YhdP slows IM rupture in a high flux GPL transport background [ 6 ]. Furthermore, a recent publication also reveals the essentiality and redundancy of YhdP, TamB, and YdbH [ 37 ]. The authors also demonstrate a disruption in OM lipid homeostasis in yhdP tamB mutants, but do not establish defects in GPL transport [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent publication also reveals the essentiality and redundancy of YhdP, TamB, and YdbH [ 37 ]. The authors also demonstrate a disruption in OM lipid homeostasis in yhdP tamB mutants, but do not establish defects in GPL transport [ 37 ]. Given the work presented here and the impressive work of our colleagues [ 6 , 37 ], it is clear that this remarkable family of proteins plays an important role in cell envelope biogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would exactly resemble the Lpt β-jellyroll bridges that provide the route for LPS molecules to be exported to the OM [5], perhaps shedding additional insights into the true nature of the enigmatic Bayer bridges. In the case of TamB, the presence of its cognate OM partner TamA is necessary for its newly-discovered function in OM lipid homeostasis [69]; in this regard, YhdP, YdbH, and other AsmA-like homologs may also require additional OM factors. E.…”
Section: Asma-like Superfamily Proteinsmentioning
confidence: 99%
“…All these observations point towards putative function(s) in membrane biology. Very recently, YhdP, TamB, and YdbH are found to be collectively essential for growth and OM homeostasis in E. coli [69,70], making them prime candidates for the critical process of PL transport. Steady-state lipid analyses revealed that cells lacking both YhdP and TamB produce more OM vesicles, and these vesicles have reduced PL:LPS ratios [70].…”
Section: Asma-like Superfamily Proteinsmentioning
confidence: 99%